The oldest censuses of clergy in the Krakow archdiocese - Jan Szczepaniak (Folia Historica Cracoviensia, 2005)
The article outlines the oldest parish and clergy catalogue of the Krakow diocese known to date. It is included in the 19th volume of Liber privilegiorum in the Wawel cathedral. The elenchus published herein is composed of two parts. The first part contains a catalogue of parishes, provosts and curates, and the second holds a list of prelates and canons of the cathedral charter house as well as collegiate charter houses. It dates back to a period between August 1751 and February 1752.